MENJAGA AKSES PENDIDIKAN YANG ADIL: TANTANGAN DAN SOLUSI DALAM PEMBIAYAAN PENDIDIKAN DI INDONESIA - Aprilliantoni; Farhan Ali Jimale (Almarhalah: Jurnal Pendidikan Islam, 2023)
Education is a basic right for every individual to develop his potential as a cultured and democratic human being. However, the higher cost of education makes access to education more difficult for people in the middle and lower economic classes. Therefore, education financing is very important in providing a fair opportunity for every individual to get a quality education. The purpose of this research is to find out the Education Funding Inclusion Policy that is equitable with the length of years of education and has a relationship with people's welfare. Where is the force of attraction between the two poles. Previous research only compared the rate of additional years of education with poverty across countries. This research method explores secondary data collected through library research which is carried out by searching relevant literature books and secondary data obtained and processed from BPS and World Bank data. And there are 27 districts/cities in Indonesia that were surveyed. The conclusion of this paper is that the Education Funding Inclusion Policy will encourage economic growth and people's welfare. Because every economic growth will create additional jobs. Referring to the concept of Newton's Law of Attraction where there is a strong attraction between fair education funding (pro-fund), with the addition of years of education (pro-education), then between two periods there will be an attractive force of attraction between one object and another and if the distance the closer it is, the greater the force of attraction, thus producing a driving force for people's welfare